100% TECHNOLOGY-MEDIATED ADMISSION IN TALLINN HEALTH CARE COLLEGE: APPLICANTS’ FEEDBACK - Ernits, Ülle; Kont, Kate-Riin (PROFESSIONAL STUDIES: Theory And Practice, 2023)
There is a broad agreement that health care and medical school admission procedure should meet several criteria, e.g. objectivity, reliability, validity, and effectiveness as the most important characteristics that entrance exams should have. The 2020 admission process was different from all the previous years’ and we expected that health care students applicants may have difficulties with web-based interviews and tests, especially in the case of vocational students who have less experience with web-based technology. The online questionnaire study was conducted to investigate the applicants’ level of satisfaction with the admission process provided by College. As the result of the current study the clear standards for online admission procedure have been developed in Tallinn Health Care College to modernize the online admission process and make it more credible and transparent for applicants. The study aims to summarize and draw appropriate conclusions and recommendations not only in X College but also in health care education institutions worldwide based on the study1